Removal of elemental mercury from coal combustion flue gas using recyclable Dy modified Mn-Fe mixed oxide nanoparticles. Issue 5 (October 2022) - Shao, Yan; Fan, Jinhang; Li, Jiayi; Yang, Jiangxiu; Wang, Yuan; Ruan, Hongcheng; Liu, Zihao; Li, Honghu; Long, Yifei; Hu, Jiangjun
Abstract: To enhance its SO2 tolerance and further improve the Hg 0 removal performance, Dy was applied to modify the Mn-Fe mixed oxide sorbent. Results showed that appropriate Dy addition promoted the Mn3 O4 formation, decreased the grain size, enlarged the surface area, increased the chemisorbed oxygen concentration and weak acid sites of sorbent, thus promoting its Hg 0 removal performance. The calcination at excessive high temperature would result in the grain growth and decrease the sorbent activity. MnFeDy0.4 -400 (with Dy/Fe molar ratio of 0.4 and calcined at 400 °C) exhibited the best Hg 0 removal performance. Around 86% Hg 0 removal could be achieved over MnFeDy0.4 -400 under 5% O2, 300 ppm NO, 1000 ppm SO2 and 3% H2 O. O2 could replenish the active oxygen species and maintain the surface metal ions at high-valent state, which was essential to Hg 0 removal. With presence of NO, abundant active nitrogenous species could form over MnFeDy0.4 -400 surface, contributing to the Hg 0 removal. Due to strong basicity, Dy species functioned as a SO2 trap agent to preserve the predominant active species Mn3 O4, thereby improving the capacity of sorbent to resist SO2 . The formation of active nitrogenous species over MnFeDy0.4 -400 would not be significantly affected by SO2 . Moreover, MnFeDy0.4 -400 had superparamagnetic property. This enabled spent MnFeDy0.4 -400 to be separated from fly ash by magnetic separation. Regeneration and stability evaluation tests manifested that MnFeDy0.4 -400 might be a promising material that could be utilized for Hg 0 removal from flue gas. Graphical Abstract: ga1 Highlights: MnFeDy0.4 -400 showed good Hg 0 removal performance and tolerance to SO2 . Appropriate Dy addition and calcination temperature contributed to nano-Mn3 O4 formation. Dy species functioned as a SO2 trap agent to preserve the predominant active species Mn3 O4 . The magnetically responsive MnFeDy0.4 -400 could be separated from fly ash by magnetic separation.